The relationship between person-job fit, person-organization fit and job performance / Nurul Fariza Razak and Nur Azamin Najwa Jamal Ab Nasir - Razak, Nurul Fariza; Jamal Ab Nasir, Nur Azamin Najwa (Faculty of Business and Management, 2016)
This research was aimed at studying the relationship between person-job fit, person-organization fit and job performance which is focused to SAJ Holdings Sdn.Bhd. (Batu Pahat Agency). In this study, the researcher was investigated the level of job performance of employees in the organization. The researchers also explored the relationship between person-job fit and job performance; and also, the relationship between person-organization fit and job performance. Other than that, the researcher also identified the dominant variable towards the job performance. The questionnaires were distributed to the full-time employees of SAJ Holdings Sdn. Bhd. and 155 questionnaires were retrieved for analysis. Based on the findings, it can be summarised that the level of job performance of the employees is high. It also can be concluded that there is a significant relationship between person-job fit, person-organization fit and job performance. Then, form the findings, it shows that person-organization fit is most dominant variable towards job performance. The discussions of the result and recommendations are discussed.